2014
DOI: 10.4103/1008-682x.129133
|View full text |Cite
|
Sign up to set email alerts
|

Androgen synthesis inhibitors in the treatment of castration-resistant prostate cancer

Abstract: Suppression of gonadal testosterone synthesis represents the standard first line therapy for treatment of metastatic prostate cancer. However, in the majority of patients who develop castration-resistant prostate cancer (CRPC), it is possible to detect persistent activation of the androgen receptor (AR) through androgens produced in the adrenal gland or within the tumor itself. Abiraterone acetate was developed as an irreversible inhibitor of the dual functional cytochrome P450 enzyme CYP17 with activity as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 116 publications
(188 reference statements)
1
40
0
1
Order By: Relevance
“…Inhibitors (e.g. abiraterone) targeting the androgen biosynthetic enzyme CYP17 have shown significant activity in patients with CRPC (8,9).…”
mentioning
confidence: 99%
“…Inhibitors (e.g. abiraterone) targeting the androgen biosynthetic enzyme CYP17 have shown significant activity in patients with CRPC (8,9).…”
mentioning
confidence: 99%
“…There has indeed been a great deal of excitement in the oncology field over recent success in going beyond the initial use of general steroid biosynthesis inhibitors, such as ketoconazole 7 , and testing of newer CYP17A1 inhibitors, such as abiraterone 8; 9; 10 to limit DHEA biosynthesis. Recent trials have suggested that the CYP17A1 inhibition strategy is indeed successful, with ~ 5 months of additional overall survival accruing to subjects receiving abiraterone who had already developed castration resistant prostate cancer 11; 12; 13; 14; 15 . There is, nevertheless, a major problem that remains to be overcome; while tumor cells develop steroid producing ability of their own, as in the case of prostate cancer 10; 13; 14; 15 , they are not the major biosynthetic source of steroid hormones in the body.…”
Section: ): the Problemmentioning
confidence: 99%
“…Recent trials have suggested that the CYP17A1 inhibition strategy is indeed successful, with ~ 5 months of additional overall survival accruing to subjects receiving abiraterone who had already developed castration resistant prostate cancer 11; 12; 13; 14; 15 . There is, nevertheless, a major problem that remains to be overcome; while tumor cells develop steroid producing ability of their own, as in the case of prostate cancer 10; 13; 14; 15 , they are not the major biosynthetic source of steroid hormones in the body. That title is clearly claimed by the adrenal, which dwarfs steroidogenic output by testes, ovaries or other organs, including adipose and the brain.…”
Section: ): the Problemmentioning
confidence: 99%
“…For most patients, AR signaling remains the primary oncogenic driver despite castrate testosterone levels, and its activation has been observed to be mediated through a multitude of mechanisms [3,6,7]. In this article, we review the major mechanisms through which AR signaling is sustained, including AR gene amplification and overexpression, AR mutations, constitutively active AR splice variants, and intratumoral androgen synthesis.…”
Section: Introductionmentioning
confidence: 98%